The Effects of Different Nitrogen Fertilizer Application Rates on Wheat (Triticum aestivum) Growth and Yield in Uruzgan - Karimi, Abdul Shakoor; Zaryal, Khalilullah; Barak, Mohammad Nasir (Journal of Natural Sciences – Kabul University, 2024)
No prior scientific study has investigated the effects of nitrogen fertilizers on wheat cultivation in Uruzgan. To address this gap, a study titled "The Effects of Different Nitrogen Fertilizer Application Rates on Wheat Growth and Yield in Uruzgan" was conducted in 1399 (2020) in an agricultural area of Uruzgan. The research aimed to evaluate the impact of various nitrogen fertilizer rates using a randomized complete block design (RCBD). Six different nitrogen application rates—control (0), 40, 80, 120, 160, and 180 kg per hectare—were tested across six treatments with three replications, resulting in a total of 18 plots. Fixed amounts of phosphorus fertilizer were uniformly applied to all treatments. Farmers in Uruzgan often struggle to determine the optimal amount of nitrogen fertilizer to achieve maximum wheat yields. Compounding this challenge, rising fertilizer costs have made adequate application unaffordable for many farmers. As a result, wheat production in the region remains suboptimal. This study was essential to provide Uruzgan's farmers with precise guidelines on the appropriate nitrogen fertilizer rates required for maximum yields under the climatic conditions of central Uruzgan (Tirin Kot). Through Allah's grace, a standard study was successfully conducted to identify the nitrogen requirements for wheat cultivation in the region. The findings are expected to benefit farmers, agricultural students, university professors, and officials in Uruzgan's Directorate of Agriculture and Irrigation. During the study, various parameters were measured, including plant height, number of leaves, and tiller count during the growth phase, as well as spike weight, 1,000-grain weight (in grams), total grain yield (kg/ha), gross return, and net return.